Rotifers diversity at Shatt Al-Arab River and Shatt Al-Basrah canal, South of Iraq, during the abnormal rising of water salinity - Ahmed, H.K.; Ghazi, A.H.H. (Mesopotamian Journal of Marine Sciences, 2022)
This study was conducted during the period from November 2009 to March 2010 when the river of Shatt Al-Arab was subjected to abnormal rising in water salinity. The diversity of rotifers was studied in three different stations included two branches of Shatt Al-Arab River: Station 1 (Al-Asafia), Station 2 (Abu Al-Khaseeb-Jecor) and Station 3 (Shatt Al-Basrah canal). The highest values of water salinity (8.6, 16.7 and 22.5‰) were found during November 2009 in St. 1, St. 2 and St. 3 respectively and the lowest values (1.5, 1.9 and 2.8‰) were recorded in March 2010 in the three stations respectively. About 26 species of rotifers were diagnosed belongs to 16 genera, about 25 species recorded in St. 1 whereas, 13 and 12 species were recorded in St. 2 and St. 3 respectively. Jaccard’s index showed presence of similarity of rotifers species between St. 2 and St. 3 compared to St. 1.